The impact of lignin source on its self-assembly in solution12. Issue 82 (5th September 2015) - Ratnaweera, Dilru R.; Saha, Dipendu; Pingali, Sai Venkatesh; Labbé, Nicole; Naskar, Amit K.; Dadmun, Mark
<x xml:space="preserve">Abstract</x> The assembly of lignin molecules from a variety of sources is followed using small angle neutron scattering. The degree of branching of the lignin molecule, which varies with source, plays a crucial role in determining their association behavior.